2000
DOI: 10.2209/tdcpublication.41.15
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the D12s66 System in the Japanese Population and Its Detection Using Degraded Dna

Abstract: The short tandem repeat (STR) polymorphism of the locus D12S66 was amplified by PCR and analyzed by denaturing polyacrylamide gel electrophoresis followed by silver staining. Among 190 DNA samples from the Japanese population, six alleles were observed. The genotypic distribution meets Hardy-Weinberg expectations, and the heterozygosity was 52.7%. When sequences of the allelic products were compared, each allelic segment was 153-173bp in size, and contained 9 to 14 GATA tetranucleotide repeat motifs. Amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In the literature, we did not ®nd the heterozygosity values for all the population groups. With the limited available data, the heterozygosity was 0.53 and 0.67 among Japanese (Minaguchi and Haga 2000) and Caucasians (Roewer et al 1992), respectively. It was in the range between 0.40 and 0.90 among Eurasian population groups (Gomolka et al 1994).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the literature, we did not ®nd the heterozygosity values for all the population groups. With the limited available data, the heterozygosity was 0.53 and 0.67 among Japanese (Minaguchi and Haga 2000) and Caucasians (Roewer et al 1992), respectively. It was in the range between 0.40 and 0.90 among Eurasian population groups (Gomolka et al 1994).…”
Section: Discussionmentioning
confidence: 98%
“…allele 8 refers to eight repeats of the core sequences. The nomenclature of the alleles for D12S66 locus was according to Minaguchi and Haga (2000) and for D12S67 locus according to Minaguchi (1997).…”
Section: Detection Of Allelesmentioning
confidence: 99%
“…However, it is not easy to locate a candidate of a certain unknown body using dental identification. They are very good sources for DNA analysis, even in cases where the specimens are highly decomposed 11,12,16) . In order to perform personal identification by DNA analysis, we have to find a source of DNA derived from the candidate, or a blood relative of the candidate.…”
Section: Introductionmentioning
confidence: 99%
“…The development of DNA studies has provided another powerful approach for identification of unknown remains and other biological evidence in the field of forensic medicine. Many studies of DNA analysis for personal identification using materials obtained from the oral-maxillofacial regions have used tooth hard tissues and dental pulp as sources of DNA 2,7,8,[17][18][19]23,24,26,29) . Several studies have shown that DNA recovered from saliva and saliva stains attached to materials such as stamps, cigarette butts, and human skin can also be used as sources for DNA analysis native to blood.…”
Section: Introductionmentioning
confidence: 99%